The Ingenious Structure of Central Rotor Apparatus in VoV1; Key for Both Complex Disassembly and Energy Coupling between V1 and Vo - Nakanishi, Atsuko; Kishikawa, Jun-ichi; Tamakoshi, Masatada; Yokoyama, Ken (PLOS ONE, 2015)
Vacuolar type rotary H+-ATPases (VoV1) couple ATP synthesis/hydrolysis by V1 with proton translocation by Vo via rotation of a central rotor apparatus composed of the V1-DF rotor shaft, a socket-like Vo-C (eukaryotic Vo-d) and the hydrophobic rotor ring. Reconstitution experiments using subcomplexes revealed a weak binding affinity of V1-DF to Vo-C despite the fact that torque needs to be transmitted between V1-DF and Vo-C for the tight energy coupling between V1 and Vo. Mutation of a short helix at the tip of V1-DF caused intramolecular uncoupling of VoV1, suggesting that proper fitting of the short helix of V1-D into the socket of Vo-C is required for tight energy coupling between V1 and Vo. To account for the apparently contradictory properties of the interaction between V1-DF and Vo-C (weak binding affinity but strict requirement for torque transmission), we propose a model in which the relationship between V1-DF and Vo-C corresponds to that between a slotted screwdriver and a head of slotted screw. This model is consistent with our previous result in which the central rotor apparatus is not the major factor for the association of V1 with Vo (Kishikawa and Yokoyama, J Biol Chem. 2012 24597-24603).